2008
DOI: 10.3233/jrs-2008-0425
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to pharmaceutical promotion techniques among healthcare professionals in the Republic of Tatarstan, Russia

Abstract: Purpose: To study attitudes of health care professionals towards pharmaceutical promotion. Methods: Intervention study. 161 questionnaires were collected and analyzed after anonymous surveys of health-care professionals (physicians and residents).Results: Nearly half of surveyed participants (53% of physicians and 44% of residents) communicated with pharmaceutical representatives 1-2 times a week. The most widespread marketing technique was pen-gifting: 93.3% of physicians and 94.7% of residents admitted recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
2
7
0
3
Order By: Relevance
“…In these environments it is perhaps unsurprising then, that writing prescriptions in return for illegal bribes from pharmaceutical companies remains a problem. [31, 32]…”
Section: Interests Of Physiciansmentioning
confidence: 99%
“…In these environments it is perhaps unsurprising then, that writing prescriptions in return for illegal bribes from pharmaceutical companies remains a problem. [31, 32]…”
Section: Interests Of Physiciansmentioning
confidence: 99%
“…Literature reported that even physicians themselves do not deny the effect of MRs on their prescribing habit . The type and frequency of interactions between physicians and MRs have received increased scrutiny from many stockholders . However, despite that, interaction between physicians and MRs continues to be among the most controversial subjects in pharmaceutical promotion studies over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite that, interaction between physicians and MRs continues to be among the most controversial subjects in pharmaceutical promotion studies over the last decade. Consequently, physicians’ attitude towards this interaction received considerable attention in the literature . However, only few studies aimed to identify physicians’ attitude towards MRs were conducted in developing countries …”
Section: Introductionmentioning
confidence: 99%
“…Aquí se utilizan diversas fuentes para recolectar datos numéricos tales como: encuestas, entrevistas estructuradas, observaciones, indicadores y evaluaciones de desempeño, información institucional y bases de datos nacionales (McLaughlin, Bush, & Zeeman, 2016). La presente investigación utiliza un amplio cuestionario bajo la misma óptica que has seguido previos estudios cuantitativos y se presentan alguna que guarda relación con el eje central del presente estudio, tales como: Impacto (Vancelik et al, 2007), Influencia (Caamaño, Figueiras, & Gestal-Otero, 2002;Siddiqi et al, 2011) , Percepción (Lieb & Scheurich, 2014;Zaki, 2014), Efecto (Chew et al, 2000;Mizik & Jacobson, 2004;Lieb & Scheurich, 2014;Ijoma et al, 2010) y Actitudes (Burashnikova, Ziganshin, & Ziganshina, 2008;Ventura et al, 2012) de la Promoción Farmacéutica en la prescripción de medicamentos desarrollados en diversos países en los últimos años.…”
Section: Tipo De Investigaciónunclassified
“…Revisión de modelos de cuestionarios previos. La elaboración del cuestionario se realizó revisando diversas investigaciones publicadas que utilizaron diversos tipos de cuestionarios en diferentes años y países (Alssageer & Kowalski, 2012;Burashnikova et al, 2008;Calderón & Rabanaque, 2014;Lieb & Scheurich, 2014;Mizik & Jacobson, 2004;Sergeant et al, 1996;Vancelik et al, 2007;Ventura et al, 2012;Zaki, 2014).…”
Section: Diseño Del Instrumento Para Obtener Los Datosunclassified